2011
DOI: 10.1007/s10584-011-0160-3
|View full text |Cite
|
Sign up to set email alerts
|

Smallholders adaptation to climate change in Mali

Abstract: This study was undertaken to assess the potential impacts of climate change on agriculture in the Sikasso region of southern Mali, as part of an effort by the U.S. Agency for International Development (USAID) to integrate climate change adaptation considerations into their development projects. The region is considered to be the breadbasket of Mali, providing a substantial amount of the country's food supplies as well as cotton for exchange earnings. The project had two components: modeling how climate change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…Interviews with extension workers confirmed the men"s observations and described declining crop yields, scarcity of water, increased pest and disease problems, deteriorating animal health and others as mainly impacts of climate change on rural development (see Zoundji et al, 2017 for similar observations). Other studies of farmers" observations confirmed the above as the main climate change impacts in Mali (Ebi et al, 2011;Diiro et al, 2016).…”
Section: Farmers' Observation Of Climate Change and Related Impactsmentioning
confidence: 71%
“…Interviews with extension workers confirmed the men"s observations and described declining crop yields, scarcity of water, increased pest and disease problems, deteriorating animal health and others as mainly impacts of climate change on rural development (see Zoundji et al, 2017 for similar observations). Other studies of farmers" observations confirmed the above as the main climate change impacts in Mali (Ebi et al, 2011;Diiro et al, 2016).…”
Section: Farmers' Observation Of Climate Change and Related Impactsmentioning
confidence: 71%
“…Further to the stakeholder consultation program, available publications showed the agricultural system in Mali is challenged by climate variability and other factors. Ebi et al (2011) and Rahman (2006) showed occurrence of many hotter and drier days over the last several decades in Mali which in turn caused scalding in cereals, disturb flowering and strongly reduce crop yield. Butt et al (2005) reported that the precipitation trend in the southern part of Mali during the years 1960 to 2005 showed significant reduction in rainfall in the wettest months (July and August), and an increase in precipitation at the beginning of the rainy season.…”
Section: Stakeholder Consultation Programmentioning
confidence: 99%
“…Located in West Africa and land locked, Mali is one of the least developed countries with an economy that relies heavily on rainfed cereal production [1]. Smallholder agricultural production is dominated by rainfed production of millet, sorghum and maize for meeting food demands and on cotton for the market.…”
Section: Introductionmentioning
confidence: 99%
“…According to Mali's Direction Nationale de la Meteorologie (DNM), Mali has become hotter and drier over the last several decades [1]. Analyses of recent temperature records showed an increase in temperature over the latter part of the 20th century.…”
Section: Introductionmentioning
confidence: 99%